A11 Alterations in the PGC-1 α dependent oxidative stress response in the R6/2 mouse model of HD. (16th November 2010) - Sandtner, H C; Fleischer, C; Lenk, T; Landwehrmeyer, G B; Lindenberg, K S
Abstract : Background: In Huntington's disease (HD), alterations in energy metabolism and mitochondrial function may result in oxidative stress. Increased levels of oxidative damage products have been reported in HD. The transcriptional co-activator PGC-1 α stimulates mitochondrial biogenesis and induces expression of many reactive oxygen species (ROS) eliminating enzymes including SOD1, SOD2, catalase and glutathione peroxidase (Gpx1). In addition, it was shown by two independent research groups that PGC-1 α transcription is changed in HD. Aims: Here we analysed the PGC-1 α dependent ROS stress response in two different mouse models for HD. Methods/techniques: The expression levels of ROS detoxifying enzymes in brain and skeletal muscle of 12-week-old R6/2 and WT mice and in 1-year-old HdhQ20/ HdhQ111 knock-in mice were determined by qPCR. The response to oxidative stress stimuli (H2O2, glutamate) were studied using primary neurons of HdhQ20 and HdhQ111. To detect a failure of ROS stress response induction, primary neurons were treated with oxidative stressors and cells were harvested after different time points of recovery for mRNA isolation and qPCR expression analysis of ROS detoxifying enzymes. Results/outcome: We found that PGC-1 α, PGC-1β, catalase, SOD1 and SOD2 were downregulated in R6/2 brain. Furthermore, PGC-1 α was also downregulated in the HdhQ111 knock-in mouse brain, but no changes in the oxidative stress response system was found. In contrast, in muscle tissue of R6/2, Pgc-1 α expression levels were unchanged while catalase was upregulated and SOD1, SOD2 and GPx1 were downregulated. In skeletal muscle of HdhQ111, PGC-1 α and PGC-1 β were upregulated and all other tested genes were unchanged. HdhQ20 and HdhQ111 primary neurons which were exposed to glutamate did not show any significant induction of the ROS detoxifying system. It is possible that the culturing conditions with regular air oxygen concentrations might have resulted in an ROS stress response and a subsequent failure of a further stress response induction being measurable. Experiments are repeated with 3% oxygen culturing conditions. Conclusions: In summary, we found more pronounced alterations of the ROS defence system in the R6/2 mouse compared with the HdhQ111 knock-in mouse. Alterations of the ROS detox system differed between skeletal muscle and brain tissue.